2013
DOI: 10.1007/s00405-013-2446-8
|View full text |Cite
|
Sign up to set email alerts
|

Priorities of head and neck cancer patients: a patient survey based on the brief ICF core set for HNC

Abstract: The International Classification of Functioning, Disability and Health Core Set for Head and Neck Cancer (ICF-HNC) covers the typical spectrum of problems in functioning experienced by patients with head and neck cancer (HNC). The major goal of the present work was to evaluate patients' priorities using the brief ICF-HNC as a starting point. A priorities assessment checklist consisting of 15 statements was created based on the 14 validated categories of the brief ICF-HNC. In a cross-sectional study, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 17 publications
2
34
0
4
Order By: Relevance
“…Second, recommendations on how to interpret and use information gathered by selected instruments are largely missing so far: cutoff values that guide clinical decision‐making are, for instance, lacking. These findings deeply support the need of developing practical guidelines to propose a standardized set of assessment tools to functional outcomes in head and neck cancer follow‐up, the ultimate goal of our multistep effort to eventually define such recommendations, as reported in this and other publications …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Second, recommendations on how to interpret and use information gathered by selected instruments are largely missing so far: cutoff values that guide clinical decision‐making are, for instance, lacking. These findings deeply support the need of developing practical guidelines to propose a standardized set of assessment tools to functional outcomes in head and neck cancer follow‐up, the ultimate goal of our multistep effort to eventually define such recommendations, as reported in this and other publications …”
Section: Discussionsupporting
confidence: 73%
“…It has been already shown that patients with head and neck cancer perceive activities and participation as well as environmental factors as equally important as body functions, for instance . Moreover, in a recent study, it is shown that priorities of patients with head and neck cancer go far beyond body functions and structures and encompass coverage of treatment expenses, ability to performing daily tasks, and having a trusting relationships with health professionals, among others . Bearing this in mind, it is strongly recommended that more weight is given to the specific assessment of activities and participation as well as environmental factors by the head and neck cancer team.…”
Section: Discussionmentioning
confidence: 99%
“…), and the high priority HNC survivors place on minimising the financial burden of cancer (Tschiesner et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In ICF, body functions are the physiological and psychological functions of body systems, and impairments are deviations or losses in body functions [38]. Both patient self-reporting and provider-reported impairments of body functions were documented in previous HNC studies using ICF [34, 35, 39]. In our study, functional status, which is impaired body functions, consisted of impaired shoulder function (ICF Code: b710 impaired mobility of joint functions), breathing impairment (ICF Code: b440 imparted respiration functions), eating impairment (ICF Code: b510 impaired ingestion functions), speaking impairment (ICF Codes: b310 impaired voice functions and b320 impaired articulation functions), and impaired body image (ICF Code: b180 impaired experience of self and time functions) [31].…”
Section: Introductionmentioning
confidence: 99%